A Computer Code for Reliability Assessment of Electrical Auxiliary System using fault tree-analysis - Fatah, A. A.; Sadik, A. Z (Sulaimani Journal for Pure and Applied Sciences, 1999)
The paper describes a code for analyzing different structures of electric power supply systems from the reliability point of view. A genral program (program -AA) is developed for finding the minimal cutsets from the fault tree of supply system and then evaluatinng the system unavailability as a function of the most significant minimal cutsets and the unavailability of primary events appearing in these critical sets for any complex auxiliary electric supply system. The program is implemented on IBM compatible personal computer by using database software /Foxpro 2.6. The results obtained from the model give a powerfull tool for the designer of supply systems from safety point of view.